Philosophy Behind Strategy : Reconstructing the Theoretical Foundation of Strategic Management in a Disruptive Era - Manurung, Gerson; Suraji, Robertus; Manurung, Adler Haymans; Sangapan, Lukman (Jurnal Bisnis dan Ekonomi, 2025)
The era of disruption challenges the relevance of conventional strategic management theories built on assumptions of stability, predictability, and structural rationality. This study aims to identify and examine the philosophical assumptions—ontology, epistemology, and axiology—underlying mainstream strategic theories, as well as evaluate their limitations in responding to the dynamics of the VUCA world. Using a critical conceptual review and philosophical inquiry approach, this study deconstructs the foundational frameworks of theories such as Porter and Mintzberg and proposes an alternative epistemology based on pragmatism (Dewey & Rorty). The findings reveal that the absence of explicit philosophical foundations leads to theoretical fragmentation and weakens the theories' ability to adapt. As a contribution, this study offers a new, more flexible, and contextual framework to address today's disruptive challenges. Its implications include the redesign of strategic theory and recommendations for more reflective and ethical organizational policies.